Development and Characterization of a Virtual Impactor Type Dust Flow Concentrator - Wang, Hongbing (My University, 2005)
A virtual impactor type dust flow concentrator was developed and an experimental investigation was performed to characterize the hydraulic and particulate matter (PM) separation performance of the device. In particular, the pressure drop characteristics, the ratio of the flow through the two branches, and the PM concentration in the minor and main branch of the flow concentrator were evaluated using experiments on a diesel exhaust rig and an air rig. Tests were performed to examine the effect of the inlet flow Reynolds number, the inlet tube lip position relative to the concentration probe, and the flow distribution between the minor and main branches. Numerical simulations were also performed for a simplified concentrator geometry to examine the flow streamlines and pressure drop. The results showed that the ratio of the concentration in the minor and main flow branches changed as the flow rate in these branches changed, reaching a maximum at a minor flow ratio that depended on the lip position. It was observed the difference of the particulate matter concentration in the minor and main branch was greater for higher inlet Reynolds number. For example, the concentration ratio increased 50% as the Reynolds number increased from 2,200 to 25,700. A similar result was observed when the inlet tube lip was moved further into the concentration body. The pressure losses seem to be mainly caused by the changes in flow directions and the change in the cross sectional areas.
Keywords: characterization, virtual impactor, type dust, flow concentrator, hydraulic, matter, pressure drop, Reynolds number